2020 3rd International Seminar on Research of Information Technology and Intelligent Systems (ISRITI) 2020
DOI: 10.1109/isriti51436.2020.9315478
|View full text |Cite
|
Sign up to set email alerts
|

The Multimodal Deep Learning for Diagnosing COVID-19 Pneumonia from Chest CT-Scan and X-Ray Images

Abstract: Due to the COVID-19 Pandemic, doctors need to make medical decisions for their patients based on many examinations (e.g., polymerase chain reaction test, temperature test, CT-Scans, or X-rays). However, transfer learning has been used in several researches and focuses on only a single modality of biomarkers (e.g., CT-Scan or X-Ray) for diagnosing Pneumonia. In recent studies, a single modality has its own classification accuracy and every different biomarker may provide complementary information for detecting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 17 publications
0
26
0
1
Order By: Relevance
“…X-ray images can be used to detect and monitor the symptoms of patients with COVID-19 ( Fig. 5 ) [ 100 ]. For instance, X-ray images of the lungs are used to detect abnormal respiration.…”
Section: Intelligent Healthcare Technologymentioning
confidence: 99%
See 2 more Smart Citations
“…X-ray images can be used to detect and monitor the symptoms of patients with COVID-19 ( Fig. 5 ) [ 100 ]. For instance, X-ray images of the lungs are used to detect abnormal respiration.…”
Section: Intelligent Healthcare Technologymentioning
confidence: 99%
“…5 Sample images of normal person and patients with COVID-19 (left) and histograms of the images (right) (reprinted from Ref. [ 100 ] with permission). …”
Section: Intelligent Healthcare Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…where t g denotes the projection of updating parameters and t v denotes the exponential average of squares gradients. The stride can de described in (16).…”
Section: ) Optimizer Functionmentioning
confidence: 99%
“…Experimental results showed that with the limited training data, most of the deeper networks struggled to train well and provided less consistency. Hilmizen et al [16] proposed a combined two different transfer learning models method for CT-Scan and CXR images classification. The authors collected 2,500 CT images and 2,500 CXR images into two classes of normal and COVID-19, in this work, they used Densenet-121, Mobile net, X-ception, Inception-v3, ResNet-50 and VGG-16 for classification.…”
Section: Introductionmentioning
confidence: 99%